2016
DOI: 10.4172/2315-7844.1000197
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Leadership and Its Effect on Students’ Academic Performance

Abstract: Introduction: Leadership in schools has been a major cause for concern, not only in our Jamaican society, but on a global level. Leaders are metaphorically viewed as anchors, as they are totally responsible for the success of their organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…The findings of this study show that instructional leadership of principles gives direct effect on students' achievement. Principal also influences students' achievement through his support to the teachers (Heaven & Bourne, 2016;Lunenburg, 2010;Neumerski, 2013). It is in line with this study findings showing that principle leadership gives direct effect on teachers' performance and gives indirect effect on students' achievement through teachers' performance.…”
Section: The Effect Of Instructional Leadership On Teacher Performancsupporting
confidence: 86%
“…The findings of this study show that instructional leadership of principles gives direct effect on students' achievement. Principal also influences students' achievement through his support to the teachers (Heaven & Bourne, 2016;Lunenburg, 2010;Neumerski, 2013). It is in line with this study findings showing that principle leadership gives direct effect on teachers' performance and gives indirect effect on students' achievement through teachers' performance.…”
Section: The Effect Of Instructional Leadership On Teacher Performancsupporting
confidence: 86%
“…This relationship was confirmed by Ross and Gray (2006) that principals contribute to student achievement indirectly through teacher commitment and beliefs about their collective capacity which was also explained in the study of Liu, et al (2020) that instructional leadership is positively and directly associated with teacher self-efficacy. However, Heaven and Bourne (2016) found a positively weak statistical correlation between the performance of students and instructional leadership. Similarly, Dutta and Sahney (2016) found that principal leadership behaviors were not associated directly with either teacher job satisfaction or school-aggregated student achievement.…”
Section: Introductionmentioning
confidence: 90%
“…This implies that failure to supervise well the teachers would result in ineffective instruction and adversely affect students' academic output. Several other studies have subsequently found a significant relationship between instructional supervision and student outcome in various countries (Comfort, Aina, & Idowu, 2017;Heaven & Bourne, 2016;Okendu, 2012;Tyagi, 2010;Veloo, Komuji, & Khalid, 2013). This finding can be argued to be true when other factors such as adequate levels of staffing are taken into account.…”
Section: The Relationships Between the Instructional Supervision Practice And Students Academic Performancementioning
confidence: 93%